Profesi Guru Perspektif Sosiologi Pendidikan - ., Ridwan (Madaniyah, 2017)
Some of the things that certainly we all share an appreciation that teachers struggle from time to time is always training and training it demonstrates the teaching professionfuture always follow the changes and the rate of development of modern science and technology capabilities personal competence of teachers needs to have the teachers are as follows: the teacher as a human God Almighty, teachers have an advantage over the others, teachers constantly dealing with different and diverse communities uniqueness of learners and people then teachers need to develop an attitude of tolerance and tolerance in addressing the differences encountered in interacting with learners and the community, teachers are expected to be a facilitator in developing the culture of critical thinking in the community, mutually accept the differences of opinion and to agree for a common goal then required a teacher to be democratic in conveying and received ideas about the problems that exist in the vicinity so that teachers be open and do not close themselves from things outside himself. The scope of service of teachers in carrying out his profession which consists of: Educational administration services;instructional services; and support services.Â Keywords: competence, the teaching profession, education.